Comparative morphology of the ileum of three species of Cephalotes (formicidae, myrmicinae) - Bution, M. L. [UNESP]; Caetano, F. H. [UNESP]; Zara, F. J. [UNESP] (My University, 2007)
The histology (H.E.), histochemistry (carbohydrates, proteins, collagen, and calcium), enzyme profile (ATPase and Acid phosphatase), and ultramorphology of the ileum of Cephalotes atratus, C. clypeatus and C. pusillus were studied in order to obtain some information about the similarities of these species. The relationship among these three species, as well as the results obtained for the wall, and the contents of this portion of the digestive tract were discussed. In C. clypeatus the ileum is somewhat smaller than that of C. atratus, despite the similarities in body size. The ATPase results showed 2 different regions: the anterior region responsible for absorbing material from the haemolymph and the posterior region for absorbtion from the ileum lumen. Other histochemical analyses failed to show any differences.
Keywords: Cephalotes; Enzymology; Formicidae; Histochemistry; Ileum; Myrmicinae; Ultramorphology; Cephalotes atratus; Cephalotes clypeatus; Cephalotes pusillus